PERANAN HUKUM PENANAMAN MODAL TERHADAP PENYELESAIAN KONFLIK ANTARA PEMERINTAH INDONESIA TERHADAP PT INDOSAT - Florentinus Sudiran, Deasy Fitriyana dan (Universitas 17 Agustus 1945 Samarinda, 2019)
This researh is labrary one about the dispute between thegovernment Indonesia and PT. Indosat. The results of the research are isthat the other countries do not trust to the government of Indonesia aboutthe illegal usage of the frequency 3G which receives te formal letter asthere is no trust to Indonesia about the process of the law inforcement (Gto G atau government to government) which is owned by Qatar. It is nowbeing processed in Great Court. This problem involed the the PT. Indosatand its group Indosat Mega Media (IM2). The solution is based n theregulation of the invesment Number 25, 2007 on conflict solution.In the Artcle 32 or he regulation concered has been determined theways of the conflict or dispute between the Governmnt of Indonesia an theDomistic investor a follows 1) Negotiation, Arbitrage, Alternative ofconflict solution and court. The suggestions (1) The Governmnt ofIndonesia ha to improve the investment climate; (2) To use the regulationof investmen Number 25 2007; (3) To give the llimit of recommendationand to publish the realization of the rgulation concerned to guarentee thethe supreme of law of the domistic regulation of regional government.